Elite-level athletes with physical impairments: Barriers and facilitators to sport participation. Issue 6 (23rd June 2022) - Ballas, Jessica; Buultjens, Melissa; Murphy, Greg; Jackson, Mervyn
Abstract: Knowledge of the often-complex psycho-social factors that influence sport participation is important to increase the number of individuals with a physical impairment participating in sport, and simultaneously enhancing social inclusion and community engagement. The present study examined the sporting experiences of ten high-performing Australian athletes with a physical impairment from grassroots to elite-level. The interviews were transcribed, and thematic analysis was performed for data synthesis. Drawing on the theory of self-determination and the social model of disability, the results highlighted increases in wellbeing including improved fitness, social interaction and self-confidence. The athletes identified primary school and high school as highly influential environments in establishing their interest in sport, with these settings also considered as fruitful platforms to support an inclusive culture and education on disability and sport amongst the wider community.